Implementación de un Supermercado de productos de consumo básico (hortalizas, verduras y frutas) producidos con abono orgánico en la ciudad de Loja, propuesta de financiamiento - Sócola Sócola, Herman Oswaldo (2016)
The main objective of this research is the "determining economic and financial feasibility for the creation of a marketer of organic aliments vacuum, in the city of Loja. This idea has been taken and initiative since in the town at present there is a company that produces organics aliments, while the population of this city has a tradition consume practically on a daily basis this grass.It is so in the present investigation will be thorough and detailed each of the studies carried out analysis to know what as feasible and beneficial results both for citizens and for investors to start the idea of this proposal. The total number of unsatisfied demand, the number of people who are not meeting their needs as they wanted to and would be willing to buy this products in supermarkets Supermaxi, Romar of the city could learn through surveys for the purpose of the study of market. Requirement; also translates the marketing mix which shows the analysis service, place, price and promotion or advertising. Reference to the technical study on everything concerning the location, capacity of production as well as different resources will be used in each of the activities. The present proposal also is administrative study that helped define the entire legal and administrative to be framed in everything required by law and thus prevent future complications. 5 Finally, he had intended to capture a financial study that reveals all the economic part of the company, where it is obtained from the initial investment ($144.951,91) until the returns that would be generated during the five years of useful life of the project; as most relevant points can be said that the company has a range of $174.842,67which shows that it is acceptable and a TIR of 49,78 percent, that would be ratifying how profitable is the investment in this proposal, it is worth mentioning that the initial capital will be recovered in two year and nine month